Immunoreactivity of the 14F7 Mab Raised against N-Glycolyl GM3 Ganglioside in Epithelial Malignant Tumors from Digestive System. (7th November 2010) - Blanco, Rancés; Rengifo, Enrique; Cedeño, Mercedes; Rengifo, Charles E.; Alonso, Daniel F.; Carr, Adriana
Abstract : The limited expression of N-Glycolyl GM3 (NeuGcGM3) ganglioside in human normal tissues, as well as its presence in melanoma and breast carcinoma using 14F7 Mab (anti-NeuGcGM3), has been previously reported. In this work we evaluated for the first time the 14F7 Mab immunorecognition in some digestive system tumors. Immunohistochemical assays were made with 14F7, followed by anti-mouse biotinylated antibody and ABC/HRP system in normal and pathological human tissues were made. No immunoreaction was evidenced in normal tissues. The reactivity of 14F7 was detected in all adenocarcinomas of the stomach (12/12), colon (12/12), and pancreas (11/11). A finely granular immunorecognition in esophageal tumors (5/15), epidermoid carcinoma of the rectum (5/7), and basaloid carcinoma (4/5) of the latter as well as in hepatocellular carcinoma (13/14) was also observed. Our results are in agreement with the assumption that NeuGcGM3 ganglioside may be considered as target for passive and active immunotherapy in digestive system malignancies expressing this molecule.